Poverty Alleviation Efforts Through Socialpreneurship in Gorontalo - Sheilla Budiawan; Afriana Lomagio (Indonesian Journal of Economics, Social, and Humanities, 2023)
This research to reveal efforts in poverty alleviation through the involvement of socialpreneurs in Gorontalo by using descriptive qualitative methods. This qualitative research has an exploratory and meaningful approach to social phenomena that actually occur. For standard determination of informants, researchers used purposive sampling technique. In this study, researchers will conduct deep interviews as a basic stage of data collection for socialpreneurs in their involvement in poverty alleviation in Gorontalo. The results of this study indicate the magnitude of the role of entrepreneurs in supporting socialpreneurship programs. This is evidenced by the fact that every entrepreneurial activity that is carried out always involves a social environment program. Several Micro, Small and Medium Enterprises (MSMEs) in Gorontalo always work together to hold a socialpreneurship program to help economic growth in Gorontalo. Several forms of socialpreneurship activities carried out by MSME actors in Gorontalo include reducing the use of plastic materials, distributing food staples assistance, and opening employment opportunities as well as helping to develop entrepreneurship in the form of resellers.